North-South trade, openness and growth - Foster, Neil (2001)
It has long been thought that openness to international trade can be beneficial to a country in terms of growth, and that trade liberalisation can assist in enhancing countries growth rates. For a long time such arguments were based on static theories, in which trade raises the level of income, but not the long-run growth rate. Recently, models have emerged that show how countries can increase their long-run growth rates through trade. Trade can affect growth through a number of channels. For developing countries however, the primary benefit that trade provides is likely to be access to the technology of more advanced countries.